Katuk Leaf tea Pengaruh Teh Daun Katuk Terhadap Kecukupan Asi Pada Bayi Umur 0 Sampai 6 Bulan di Puskesmas Lahei II Kapubaten Barito Utara: The Effect of Katuk Leaf Tea on Breast Milk Adequacy in Infants Aged 0 to 6 Months at Lahei II Health Center in North Barito Regency - Kaleluni, Tiana Kaleluni Tiana; Happy Marthalena Simanungkalit; Irene Febriani (Jurnal Forum Kesehatan : Media Publikasi Kesehatan Ilmiah, 2025)
The benefits of breastfeeding according to WHO protect babies from germs, provide complete nutrition, guarantee hygienic and safe intake, make babies grow healthy and smart, reduce cancer risk, help give birth spacing, save costs. Katuk is a plant of local wisdom (indigenous), which is popular in South Asia and Southeast Asia, including Indonesia. This plant has many benefits, especially to increase milk production for nursing mothers so that mothers can meet the adequacy of breast milk for their babies. The objective of this research is to determine the effect of katuk leaf tea on the adequacy of breast milk in infants 0 to 6 months at Lahei II Public Health Center, North Barito Regency. This study used a quasi-experimental or quasi-experimental research design with pretest posttest non-equivalent control group design. The sampling technique used purposive sampling with a total sample of 17 mothers who were breastfeeding by consuming katuk leaf tea and 17 mothers who were breastfeeding who were not given treatment as controls. This study was analyzed using the Wilcoxon test. The resulting z-test statistic is -2.270 with a probability of 0.023. This means that the probability is < (0.05), thus it can be stated that there is a significant difference in the adequacy of breastfeeding on the 8th day in the intervention group with the adequacy of breastfeeding on the 8th day in the control group. For breastfeeding mothers, they can consume katuk leaf tea to increase milk production so that they can provide exclusive breastfeeding to their babies until the age of 6 months.